Predictors of Insulin Treatment During Pregnancy and Abnormal Postpartum Glucose Metabolism in Patients with Gestational Diabetes Mellitus - Tang L; Xu S; Li P; Li L (Diabetes, Metabolic Syndrome and Obesity, 2019)
Lei Tang,1 Shiting Xu,1 Ping Li,1 Ling Li1,2 1Department of Endocrinology, Shengjing Hospital Affiliated to China Medical University, Shenyang, Liaoning Province, People’s Republic of China; 2Liaoning Province Key Laboratory of Endocrine Diseases, Shenyang, Liaoning Province, People’s Republic of ChinaCorrespondence: Ling LiDepartment of Endocrinology, Shengjing Hospital Affiliated to China Medical University, No. 36, Sanhao Street, Heping District, Shenyang, Liaoning Proving, People’s Republic of ChinaTel +86 18940251181Fax +86 024-25944460Email liling8864@hotmail.comBackground: To investigate the potential predictors of insulin treatment during pregnancy and abnormal postpartum glucose metabolism in gestational diabetes mellitus (GDM).Methods: A total of 534 patients with GDM, who were diagnosed based on 75 g oral glucose tolerance test (OGTT) during pregnancy, were divided into the diet group (n=354) and insulin group (n=180) according to the treatment of hyperglycemia in pregnancy. Based on 75 g OGTT after delivery, 178 of the 534 patients were divided into the normal glucose tolerance (NGT; n=104) and the abnormal glucose tolerance (AGT; n=74) groups. Characteristics and metabolic indicators were compared. Logistic regression analysis was developed to assess the potential predictors of insulin treatment and abnormal postpartum glucose metabolism. Receiver operating characteristic curve was performed to determine the cut-off values.Results: Fasting plasma glucose (FPG), 1 h plasma glucose, and hemoglobin A1c (HbA1c) at GDM diagnosis were higher in the insulin group compared with the diet group (P <0.05). FPG, 1 h plasma glucose, HbA1c, maternal age, pre-gestational weight and maximum weight, pre-gestational body mass index, maternal birth weight, family history of diabetes in first-degree relatives, acanthosis nigricans, and prenatal weight were risk factors for insulin treatment (P <0.05), and the cut-offs of FPG, 1 h plasma glucose and HbA1c were 5.7 mmol/L, 11.4 mmol/L and 5.3%. Simultaneously, FPG at GDM diagnosis, insulin treatment during pregnancy, maternal age, family history of diabetes in first-degree relatives, acanthosis nigricans, and prenatal weight were risk factors of abnormal postpartum glucose metabolism (P <0.05), and the cut-off of FPG was 5.7 mmol/L.Conclusion: Patients with FPG >5.7 mmol/L, 1 h plasma glucose >11.4 mmol/L, or HbA1c >5.3% at GDM diagnosis required insulin treatment, and patients with FPG >5.7 mmol/L had a greater risk of abnormal postpartum glucose metabolism. FPG at GDM diagnosis was the most important predictor.Keywords: gestational diabetes mellitus, insulin treatment, postpartum glucose metabolism